Integrating Behavior and Physiology Into Strategies for Amphibian Conservation - Walls, Susan C.; Gabor, Caitlin R. (Frontiers in Ecology and Evolution, 2019)
The amphibian decline crisis has been challenging to address because of the complexity of factors—and their multitude of interactive effects—that drive this global issue. Dissecting such complexity could benefit from strategies that integrate multiple disciplines and address the mechanistic underpinnings of population declines and extirpations. We examine how the disciplines of behavior and physiology could be used to develop conservation strategies for amphibians and identify eight research gaps that provide future directions for the emerging fields of conservation behavior and conservation physiology. We present two case studies on imperiled salamanders that show how studies of behavior and physiology may support amphibian conservation efforts. We found several applications of stress physiology to amphibian conservation, but long-term studies are needed to understand how stress ultimately affects individual fitness and population resilience. Additionally, multiple measures of physiological health are needed to provide a more holistic assessment of an individual’s overall condition. Previous behavioral and physiological studies have been instrumental for understanding how amphibians respond to habitat modification, pathogens and parasites, contaminants, and invasive species. Some behavior-based approaches to mitigating invasive species issues have been successful in short-term studies with individual species. However, widespread application of these tactics has not yet been integrated into conservation and management strategies for ecologically-similar species. A diversity of modeling approaches has enhanced understanding of how climate change may impact amphibian populations, but model predictions need empirical tests to provide conservation managers with workable approaches to multiple perturbations associated with global environmental change. We illustrate that behavior and physiology can have broad utility for amphibian conservation, but evidence is scant that such studies have actually been used to inform strategies for amphibian conservation and management.